Indirect evidence for Delta-dependent intracellular processing of Notch in Drosophila embryos. - Lecourtois, M.; Schweisguth, F. (Current Biology, 1998)
Cell-cell signaling mediated by the receptor Notch regulates the differentiation of a wide variety of cell types in invertebrate and vertebrate species, but the mechanism of signal transduction following receptor activation is unknown. A recent model proposes that ligand binding induces intracellular processing of Notch; the processed intracellular form of Notch then translocates to the nucleus and interacts with DNA-bound Suppressor of Hairless (Su(H)), a transcription factor required for target gene expression. As intracellular processing of endogenous Notch has so far escaped immunodetection, we devised a sensitive nuclear-activity assay to monitor indirectly the processing of an engineered Notch in vivo. First, we show that the intracellular domain of Notch, fused to the DNA-binding domain of Gal4, regulated transcription, in a delta-independent manner. Second, we show that full-length Notch, containing the Gal4 DNA-binding domain inserted 27 amino acids carboxy-terminal to the transmembrane domain, activated transcription in a delta-dependent manner. These results provide indirect evidence for a ligand-dependent intracellular processing event in vivo, supporting the view that Su(H)-dependent Notch signaling involves intracellular cleavage, and transcriptional regulation by processed Notch.